Kusta dalam Lensa Teologi dan Medis: Pemahaman Interdisipliner dari Imamat 13 - Kumoro Adiatmo; Simon Simon; Steven Tommy Dalekes Umboh (Sekolah Tinggi Teologi Ekumene Jakarta., 2024)
Modern medical literature reveals that leprosy is a treatable disease and not easily contagious. In contrast, theological literature, especially from biblical texts, often views leprosy as a symbol of sin and impurity, reinforcing social stigma against sufferers. This study combines theological and medical perspectives to provide a more comprehensive understanding of leprosy, focusing on Leviticus 13. Using descriptive qualitative methods and a literature review, this research analyzes various sources. The results indicate that ancient theological views of leprosy as divine punishment have perpetuated enduring social stigma. Meanwhile, modern medical perspectives offer scientific explanations that emphasize leprosy as a treatable medical condition, helping to reduce this stigma. This study suggests concrete steps to reduce stigma, such as community education, social integration of leprosy sufferers, empathy training for healthcare workers, and psychosocial support. This research not only enhances understanding of leprosy from historical and theological viewpoints but also provides practical ways to address social stigma and support the reintegration of leprosy sufferers into society.